Conversion and recovery of saponifiable lipids from microalgae using a nonpolar solvent via lipase-assisted extraction. (July 2018) - Law, Sam Q.K.; Halim, Ronald; Scales, Peter J.; Martin, Gregory J.O.
Graphical abstract: The graphical illustration shows the proposed mechanisms of how saponifiable lipids of different polarity can be converted to fatty acid methyl esters (FAME) in a hexane-emulsified microalgae slurry. This allows a biomass with high polar lipid and high moisture (ca 80% water) content to be used as a transesterification feedstock. In addition, the polar saponifiable lipids recovery is enhanced compared to a conventional hexane extraction process, allowing the recovery of valuable eicosopentaenoic acids (EPA) typically associated with polar lipids. Highlights: Ruptured Nannochloropsis slurry was used as a feedstock for biodiesel production. TAG and polar lipids were converted to biodiesel and recovered in hexane. Two pathways for converting and recovering polar lipids were identified. The water in slurry buffered the lipase inhibition caused by excess methanol. Unrecovered methanol poses a challenge for biodiesel-only application. Abstract: A single-step method for transesterifying and recovering lipids in concentrated slurries ( ca 20% w/w solids) of ruptured microalgae is presented. A soluble Rhizomucor miehei lipase (RML) was used to directly transesterify the lipids in the marine microalgae Nannochloropsis salina . This allowed both triglycerides (TAG) and polar saponifiable lipids to be recovered as fatty acid methyl esters (FAME) using a nonpolar solvent (hexane). Up to 90 wt% of the total saponifiable lipids (SL) were converted to FAME within 24 h, approximately 75% of which was recovered in the hexane by centrifugation. Two pathways for the conversion and recovery of polar lipids were identified. The water in the slurry buffered against potential lipase inhibition by methanol, but necessitated a high methanol dose for maximal FAME conversion. Nonetheless the method enables the recovery of polar lipids as FAME while avoiding the need for both drying of the biomass and a downstream transesterification step.